Knowledge, Attitude, and Practice in Choking Management among Toddlers: A Scoping Review - Pige Rade Sairo; I Ketut Swarjana; I Ketut Alit Adianta; Ni Komang Tri Agustini (GLOBAL HEALTH SCIENCE GROUP, 2025)
Choking remains a leading cause of morbidity and mortality among children under five, commonly triggered by food and small objects, yet community knowledge and practices are often inadequate. This scoping review aimed to map existing evidence on educational interventions for paediatric choking management among toddlers. Literature searches were conducted in PubMed, Science Direct, and other databases for studies published published in 2019-2024, applying the PICO framework targeting parents, teachers, caregivers, and healthcare providers. The initial search identified 674 records, with 14 studies meeting inclusion criteria after systematic screening. Studies employed pre-experimental, quasi-experimental, cross-sectional, or randomised designs with sample sizes ranging from 30-447 participants. Educational interventions using audiovisual media, demonstrations, counselling, and simulations consistently enhanced knowledge and skills, with audiovisual approaches showing the most notable effects. Despite improvements in knowledge acquisition, gaps remained between theoretical understanding and practical application in real-life choking incidents. This review contributes to the scientific literature by providing comprehensive mapping of effective educational strategies and identifying the persistent theory-practice gap, informing evidence-based intervention design for enhanced community preparedness.